The Content of Religious Broadcasting in the Mass Media and Its Implications for the Community - Sarbini, Ahmad (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2018)
In the midst of massive online media and social media content, the role of electronic mass media such as television and radio is still considered to have important values and strategic positions in building civil society. Sociological implications of healthy and educational religious broadcast content are expected to be able to become ammunition to build noble values in people's lives. The research aims to find out how the considerations of the broadcasters' management in formulating religious content, and also the sociological implications that emerge in response to the broadcasts or religious broadcasts of radio and television media. The research also aims to determine the level of government concern for broadcasting institutions in realizing religious broadcast content. In accordance with the objectives of the study, qualitative methods are the choice of researchers. Data collection is done through observation, interviews, and documentation studies. The study resulted in conclusions that broadcasters' managers in packaging and formulating the concept of religious broadcasting were based more on idealistic sociological considerations than the consideration of materialistic pragmatism. Referring to the community response, it is also evident that religious broadcast content has sociological implications that not only give birth to better religious insights and awareness, but also bring out more religious attitudes and behaviors as one of the important indicators of civil society. In the view of broadcasting managers, the level of government concern is still relatively minimal.